PENGARUH BUDAYA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI TATA USAHA DALAM PENGELOLAAN ADMINISTRASI - Hasan, Yulfian; Hendriani, Suswati; Herlina, Elda (Jurnal Dedikasi Pendidikan, 2024)
This research aims to determine the influence of culture and work discipline on employee performance in state high schools throughout Solok Regency. This research uses a type of correlation research. The population in this study was all State High School Administration employees in Solok Regency, totaling 65 people. The research instruments used were work culture questionnaires, work discipline questionnaires and employee performance questionnaires. The data collection technique used was distributing questionnaires to respondents who were classified as research samples. The research used was a closed questionnaire. To analyze the data, researchers used analytical techniques by carrying out classical assumption tests as a prerequisite test, then carrying out simple linear regression analysis and multiple linear regression analysis. The results of the research show that 1) work culture has a positive and significant effect on the performance of Administration employees by 72.8%, 2) work discipline has a positive and significant effect on the performance of Administration employees by 72.7%, 3) culture and work discipline together -sama has a positive and significant effect on the performance of Administration employees by 78.1%. The conclusion from the research that has been conducted states that work culture and discipline have a positive and significant effect on the performance of Administrative employees in administrative management